CONTINUOUS IMPROVEMENT DAN PENGELOLAAN KEPUASAN PELANGGAN BERBASIS DATA - Luluk Rosyidatul Umah; Siti Aimah (STKIP Pesisir Selatan, 2026)
This study aims to develop and evaluate a customer satisfaction management model that integrates a data-driven continuous improvement approach in the school environment. Using a qualitative design with a case study at Darussalam Elementary School in Blokagung, Banyuwangi, this study involved key informants such as the Principal, Vice Principal for Curriculum, teachers, and parents who were selected purposively. Data were collected through observation, semi-structured interviews, and documentation, which were then systematically analyzed through data reduction, presentation, and verification. The results show that the implementation of a real-time student data dashboard has shifted the school's management culture from intuition-based to evidence-based management. Teachers have transformed into active data collectors and analysts, while parents have become strategic partners in providing feedback through digital channels for decision-making. This research contribution confirms that successful customer satisfaction management depends not only on digital technology but also on the capacity of social actors to build a collaborative, transparent, and adaptive educational ecosystem through a continuous improvement cycle. Practically, this model provides guidance for educational institutions to systematically increase accountability and responsiveness to external and internal customer needs